Catalytic Conversion of Alcohols into Carboxylic Acid Salts in Water: Scope, Recycling, and Mechanistic Insights. Issue 12 (14th June 2016) - Zhang, Lei; Nguyen, Duc Hanh; Raffa, Guillaume; Trivelli, Xavier; Capet, Frédéric; Desset, Simon; Paul, Sébastien; Dumeignil, Franck; Gauvin, Régis M.
Abstract: Invited for this month′s cover are the groups of Franck Dumeignil and Régis Gauvin at the University of Lille. The image illustrates the oxidation of alcohols by ruthenium complexes in and by water, with release of hydrogen as the only co‐product. The Full Paper itself is available at10.1002/cssc.201600243 . Abstract : "The reaction described herein is a perfect example of success…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201600243 . View the Front Cover here:10.1002/cssc.201600764 .